The Economics of Health and health care - Folland, Sherman; Goodman, Allen C.; Stano, Miron (Upper Saddle River, N.J. ; [Great Britain] : Prentice Hall, 2001)
For courses in Health Economics, U.S. Health Policy/Systems, or Public Health, taken by health services students or practitioners. Students in this course have varying backgrounds in Economics-Folland's text makes Economics concepts the backbone of the Heath Care coverage. Folland is the best-selling Heath Care Economics text that teaches through core economic themes rather than concepts unique to the health care economy. The Sixth Edition retains the text's hallmark features while updating content to reflect the major changes in the health policy arena. The core economics themes chosen are as basic as supply and demand, as ever-present as technology or labor issues, and as modern as the economics of information.
Introduction -- Microeconomic Tools for Health Economics -- Statistical Tools for Health Economics -- Economic Efficiency and Cost Benefit Analysis -- Production of Health -- The Production, Cost, and Technology of Health Care -- Demand for Health Capital -- Demand and Supply for Health Insurance -- Consumer Choice and Demand -- Asymmetric Information and Agency -- The Organization of Health Insurance Markets -- Managed Care -- Nonprofit Firms Nonprofit Firms -- Hospitals and Long-term Care -- The Physician's Practice -- Health Care Labor Markets and Professional Training -- The Pharmaceutical Industry -- Equity, Efficiency and Need -- Government Intervention in Health Care Markets -- Government Regulation: Principal Regulatory Mechanisms -- Social Insurance -- Comparative Health Care Systems and Health System Reform -- Health System Reform -- The Health Economics of Bads -- Epidemiology and Economics: HIV/AIDS in Africa
Includes bibliographical references and index.
1
Keywords: Medical economics